On‐Load Impedance Measurements on Automotive Lithium‐Ion Cells. Issue 4 (10th November 2021) - Calles, Simon; Ulke, Jakob; Heitjans, Paul; Börger, Alexander
Abstract: The contribution presents examples for electrochemical impedance spectroscopy data taken on automotive lithium‐ion battery cells. Discharge was done with the help of an external load. The measurements were done with an initial state of charge of about 97 %, at 23 °C and from 5000–0.1 Hz. Spectra were fitted with an equivalent circuit containing two RC elements and an inductance. For load currents up to 20 A and in certain regions of the used frequency range, it is possible to measure impedance spectra also under load that almost coincide with load‐free spectra. Abstract : Electrochemical impedance spectra taken on automotive lithium‐ion battery cells with the help of an external load show for load currents up to 20 A and in certain regions of the used frequency range that impedance spectra also under load almost coincide with load‐free spectra.